PENGARUH KONSELING KELOMPOK DENGAN TEKNIK COGNITIVE RESTRUCTURING TERHADAP PENURUNAN FEAR OF MISSING OUT (FOMO) SISWA DI SMA PEKANBARU - Ledis Pazila; Tri Umari; Kiki Mariah (STKIP Subang, 2026)
This study aimed to determine the effect of group counseling services using cognitive restructuring techniques in reducing Fear of Missing Out (FoMO) among students at SMA X Pekanbaru. The study employed a One Group Pretest-Posttest experimental method involving 6 students with high FoMO levels. Data were collected through a valid and reliable FoMO questionnaire (Cronbach’s Alpha = 0.722). After participating in six counseling sessions, the results of the Wilcoxon and N-Gain analyses indicated a significant reduction in FoMO levels. The cognitive restructuring technique helped students transform irrational thoughts into more rational ones and improve self-control in social media use. Therefore, group counseling services using cognitive restructuring techniques were proven effective in reducing students’ FoMO levels.